Catalytic tandem dehydrochlorination–hydrogenation of PVC towards valorisation of chlorinated plastic waste. Issue 16 (4th April 2023) - O'Rourke, Galahad; Hennebel, Tess; Stalpaert, Maxime; Skorynina, Alina; Bugaev, Aram; Janssens, Kwinten; Van Emelen, Lisa; Lemmens, Vincent; De Oliveira Silva, Rodrigo; Colemonts, Christel; Gabriels, Philippe; Sakellariou, Dimitrios; et al.
Abstract : Solvent-based tandem conversion of PVC to PE-like material using hydrogen as atom economic reagent. Abstract : Chemical treatment of end-of-life PVC at high temperature often results in the formation of polyacetylene and eventually aromatic char. These insoluble conjugated polymers lead to industrial reactor blockages, and limit the efficiency in recycling chlorinated plastic waste. To address this challenge, a solvent-based tandem dehydrochlorination–hydrogenation process is proposed for the conversion of PVC to a saturated polymer backbone. When combining tetrabutylphosphonium ionic liquids and homogeneous Rh catalysts under H2 pressure, 81% dehydrochlorination is reached in 2 h, with the hydrogenation proceeding smoothly with minimal catalyst use of 0.5–2.0 mol% Rh. This process for PVC dechlorination yields soluble products that lack aromatics, have high degrees of dechlorination and possess a tunable content of double bonds. The chemical structures of the partially unsaturated polymer products and of the different structural motifs in the product are accurately monitored by a liquid 1 H-NMR method. Finally, X-ray absorption spectroscopy (XAS) sheds light on the catalytic Rh species during the tandem process, which are stabilized by the ionic liquid. This tandem process enables rapid PVC conversion to a saturated organic product, with polyethylene segments giving the opportunity for ensuing recycling steps.